(untitled) (Journal of Scientific Research, 2021)
In this paper, a systematic approach is designed for investigating the hybrid projective synchronization (HPS) in identical chaotic Hamiltonian systems based on Hénon-Heiles Model by using active control method (ACM). Initially, an active control law is described to achieve asymptotic stability of state vectors of given system using Lyapunov stability theory (LST). Additionally, numerical simulations utilizing MATLAB toolbox are presented to validate the efficiency and effectiveness of the designed approach. Furthermore, the proposed strategy has numerous applications in encryption and secure communication.